Expressão de aquaporinas (AQPS 1 e 9) nos ductos eferentes e epidídimo de ratos Wistar com obesidade induzida induzida por dieta de cafeteria - Ferreira, Leonardo Eduardo (2013)
The induction of obesity in experimental animals with cafeteria diet simulates the high-calorie food that humans eat, nowadays, thus enabling to study obesity and comorbidities resulting from this condition. The male reproductive system is directly affected by obesity with increased lipid peroxidation, increase of apoptotic bodies, changes in parameters espermatobioscópicos and reduced fertility. The aim of the study was to evaluate whether there are changes caused by obesity in epithelia of efferent ducts and epididymis , both in relation to morphology and expression of aquaporins 1 and 9 ( AQPs 1 and 9 ) in adult Wistar rats . After weaning , the animals were randomly divided into two groups : control group ( CON ) received standard diet and water ad libitum ( n = 10 ) and group cafeteria ( CAF ) , which received cafeteria diet soda and degassed ad libitum ( n = 10). The treatment group CAF began after the 12th week of life, totaling 40 weeks of consumption of cafeteria diet, being all dead animals with 52 weeks of age. The efferent ducts , along with initial segments ( Si ) , head ( Cç ) , body ( Co ) and tail ( Cd ) epididymis were submitted to routine histological and immunohistochemical staining for AQP- 1 and AQP- 9 . In the present study we evaluated the data: body mass, length nasoanal, waist circumference, Lee index and retroperitoneal fat mass and perigonadais; also evaluated dimensions, using morphometry and morphology of the epithelia of the efferent ducts and segments Si, Cç, Co and Cd epididymis and analyzed the expression of AQP- 9 and AQP- 1 in the efferent ducts and epididymal segments above. Changes in expression of AQPs in the efferent ducts and the epididymal epithelium were observed with increased expression of AQP- 1 and AQP- 9 reduction in efferent ducts and epididymal cauda, respectively, in animals treated with cafeteria diet. Also, there were morphological changes in the epididymal epithelium, such as increasing the number and size of cells and clear halo; increased endocytic organelles, and heterogeneous distribution of stereocilia, in animals with diet-induced obesity cafeteria. Given the results, it is believed that these changes should cause a profound impact on the luminal environment and interfere in the transport process, maturation, maintenance, protection and storage of sperm, being responsible for obesity alter the expression of AQP- 1 in efferent ducts, AQP- 9 in the epididymal cauda, the relative distribution of cells and clear halo and morphological characteristics of these parts via the sperm. However, more studies are needed to elucidate the specific mechanisms by which the cafeteria diet affects sperm morphology via specifically efferent ducts and epididymal ducts